An Integrated SCADA–PLC–HMI Model for Low-Cost Control and Real-Time Monitoring of Three-Phase AC Motors - Supratno, Setyo; Moh. Khairudin (JURNAL NASIONAL TEKNIK ELEKTRO, 2025)
Efficient and flexible control systems for remote real-time monitoring are highly needed by modern industries. Supervisory Control and Data Acquisition (SCADA) has become a core technology in automation. Most commercial SCADA systems, however, are costly and complex, thus limiting their adoption in small industries and educational institutions. Therefore, this study develops an integrated SCADA–PLC–HMI model for low-cost control and real-time monitoring of three-phase AC motors. The model is designed as an economical, portable, and user-friendly system that supports various control configurations, including Direct On-Line (DOL), Forward-Reverse, and Star-Delta. Adopting the ADDIE (Analyze, Design, Develop, Implement, and Evaluate) model, the development process involves needs analysis, system design, hardware/software development, system implementation, and performance evaluation through testing and data logging. Experimental results show that the system can alternately operate two three-phase motors, present real-time monitoring through the HMI, and automatically record operational data. The log file records system validity, operating time, and Start/Stop button responses, with timers operating at the configured 5-second delay. Motor 1 and Motor 2 run as programmed, with Motor 2 operating for 14 seconds before shutting down. These findings confirm that the proposed SCADA–PLC–HMI system is reliable, efficient, and cost-effective, thus providing a practical solution for motor control that is both affordable and adaptable. This study contributes to supporting competency development in engineering education and offers a viable automation alternative for small- and medium-scale industries.